Entanglement of Gaussian states and the applicability to quantum key distribution over fading channels - Usenko, Vladyslav C.; Heim, Bettina; Peuntinger, Christian; Wittmann, Christoffer; Marquardt, Christoph; Leuchs, Gerd; Filip, Radim (New Journal of Physics, 2012)
Entanglement properties of Gaussian states of light as well as the security of continuous variable quantum key distribution with Gaussian states in free-space fading channels are studied. These qualities are shown to be sensitive to the statistical properties of the transmittance distribution in the cases when entanglement is strong or when channel excess noise is present. Fading, i.e. transmission fluctuations, caused by beam wandering due to atmospheric turbulence, is a frequent challenge in free-space communication. We introduce a method of fading discrimination and subsequent post-selection of the corresponding sub-states and show that it can improve the entanglement resource and restore the security of the key distribution over a realistic fading link. Furthermore, the optimal post-selection strategy in combination with an optimized entangled resource is shown to drastically increase the protocol's robustness to excess noise, which is confirmed for experimentally measured fading channel characteristics. The stability of the result against finite data ensemble size and imperfect channel estimation is also addressed. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05